Tailoring diradicaloid properties of expanded isophlorinoids with systematic core-modification - Ambhore, Madan D.; Shukla, Pragati; Gonnade, Rajesh G.; Anand, Venkataramanarao G. (Chemical Communications, 2022)
Herein, we describe the synthesis, structural diversity and diradicaloid characteristics of 38 pi core-modified aromatic expanded isophlorins with eight heterocyclic rings. The diradicaloid character of expanded isophlorinoid macrocycles was engineered by systematic structural modification. Depending on the nature of the link between the heteroatoms, they adopt planar and non-planar conformations. This large structural variation with a significant difference in the extent of aromaticity is correlated with the magnitude of their respective diradical character.